Domestic Tourism in Russian Federation: Population Estimations, Resources and Development Constraints - FROLOVA, Elena Victorovna; RYABOVA, Tatyana Mikhailovna; KABANOVA, Elena Evgen'evna; ROGACH, Olga Vladimirovna; VETROVA, Ekaterina Alexandrovna (Journal of Environmental Management and Tourism; Vol 8 No 2 (2017): JEMT Volume VIII Issue 2(18) Spring 2017, 2017)
Russia is the country of contrasts, the country with a great tourist and recreational potential and rich cultural and historical heritage, but the Russian domestic tourism figures are relatively low. In this regard, according to the authors' opinion, the study of factors that prevent the development of Russian territory tourist attractiveness by the analysis of social expectations, preferences and the satisfaction of tourists with proposed domestic market of tourist services is very important one. The empirical base was represented by the results of the study conducted by All-Russian Council of Local Self-Government (with the participation of authors) in order to analyze the tendencies of tourist and cultural potential development in respect of Russian Federation municipal entities and the determination of limiting factors in the activities of local authorities. The sample consisted of 514 experts (heads of local authorities from Russian Federation municipal bodies). There was also a sociological study conducted by the team of authors in the municipal districts of Moscow region, during which 680 people were interviewed. Questionnaire survey was the leading research method. The performed study and the analysis of tourism industry development factors allowed to determine a number of problems that hinder the development of domestic tourism in Russian Federation: an underdeveloped tourist infrastructure, a poor quality of service (unprofessional staff), weak promotion of a national tourist product and area image, the absence of national tourism industry promotion, the lack of effective mechanisms for investment climate state stimulation in Russian tourism industry. Expert survey results showed that infrastructure problems become the main reason for territory competitiveness reduction within the tourist market for most municipalities in present conditions. In order to address the identified problems related to the lack of funding or the absence of finance in municipalities, the authors propose and justify the introduction of local tourist taxes. The solution of the problem concerning an insufficient level of information and advertising support for the local tourism potential and the promotion of domestic tourism product is considered by the authors as the development of an interactive general "Russian Federation tourist map" published in Internet.